Bessel, ed. Life in the Third Reich - Lowry, Bullitt (Teaching History: A Journal of Methods, 1991)
In Life in the Third Reich, Richard Bessel edits and contributes to a collection of essays on the Nazi experience. The contributors, eight of them, have written brief, undocumented essays on subjects to do with Hitler’s Germany. In the majority of cases those authors have written on the same or allied subjects at greater length elsewhere, and thus the lack of footnotes and bibliography (except for a brief "Suggestions for Further Reading") is not disabling.